Design of Accrual-Based Accounting Information System Using Full Costing Method - Dewa Ayu Giovany Angga Indrya (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2026)
Accounting Information Systems (AIS) play an important role in supporting organizational decision-making by providing accurate and timely financial information. The adoption of accrual-based accounting is particularly essential for organizations engaged in production activities, as it enables more reliable recognition of revenues and expenses and supports transparent financial reporting. However, many organizations still rely on manual or cash-based accounting practices, which often lead to inaccurate cost calculations, incomplete financial information, and limited support for managerial decision-making. This research is motivated by the need to integrate accrual accounting principles with a comprehensive cost calculation approach to overcome these limitations. This study proposes the design and implementation of an accrual-based Accounting Information System that applies the Full Costing method to allocate both direct and indirect production costs, including direct materials, direct labor, and manufacturing overhead. The main contribution of this research lies in the integration of accrual-based transaction processing and Full Costing calculations within a unified system that supports accurate cost determination and financial transparency. The proposed system was evaluated through functional testing and user validation to assess its effectiveness in transaction recording, cost calculation, and financial reporting. The evaluation results indicate that the system improves data consistency, reduces manual processing errors, and generates more comprehensive cost and financial reports compared to conventional accounting practices. Despite these positive results, the current system implementation relies on static cost allocation rules. Future work will focus on enhancing the system by incorporating dynamic cost drivers, advanced analytical features, and integration with other enterprise systems to improve scalability and decision-support capabilities.